Alternative Dispute Resolution: Effective Solutions Outside the Courts - Khoirul Anam (Penerbit Hellow Pustaka, 2026)
Out-of-court dispute resolution, known as Alternative Dispute Resolution (ADDR), offers a more flexible, efficient, and cost-effective solution compared to formal litigation. ADRs include mechanisms such as mediation, conciliation, and arbitration, which enable parties to reach agreements more quickly and constructively without going through lengthy court procedures. In the Indonesian context, ADRs serve to reduce the caseload in courts, increase the efficiency of the legal system, and maintain relationships between parties through dialogue that prioritizes deliberation and consensus. However, challenges such as a lack of public understanding, limited expertise, and the relatively high cost of arbitration remain major obstacles to ADR implementation. This study uses a descriptive qualitative approach to analyze the advantages, challenges, and effectiveness of ADRs in the Indonesian legal system. The results indicate that ADRs can be an effective solution for dispute resolution, but require strengthening regulations, institutional capacity, and public education to increase their success.